Activation of ITER materials in JET: nuclear characterisation experiments for the long-term irradiation station. (5th July 2018) - Packer, L.W.; Batistoni, P.; Bradnam, S.C.; Colling, B.; Conroy, S.; Ghani, Z.; Gilbert, M.R.; Jednorog, S.; Łaszyńska, E.; Leichtle, D.; Lengar, I.; Mietelski, J.W.; et al.
Abstract: This paper details progress in experimental characterisation work at JET for the long-term irradiation station, conducted as part of a project to perform activation experiments using ITER materials. The aim is to take advantage of the significant 14 MeV neutron yield expected during JET operations to irradiate samples of materials that will be used in the manufacturing of ITER tokamak components, such as Nb3 Sn, SS316L steels from a range of manufacturers, SS304B, Alloy 660, W, CuCrZr, OF–Cu, XM-19, Al bronze, NbTi and EUROFER. This paper presents an assessment of the nuclear environment at the relevant irradiation locations at JET, measured using a range of high purity dosimetry foils: Ti, Ni, Y, Fe, Co, Sc, and Ta, irradiated with fusion neutrons at JET over a period of 15 months. Experimental results are presented and compared to simulation predictions using a JET MCNP model coupled with the FISPACT-II inventory code. Comparisons are made for a total of 11 nuclear reactions using a range of nuclear data libraries in calculations.